Implementation of Concept Learning Model to Improve Creative Thinking Ability of Chemistry SMA Negeri 1 Galesong Utara - Ahmar, Dewi Satria (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2017)
The learning concept is divided into two namely the formation of concepts and the achievement of concepts. This learning is presented in the form of examples and definitions that lead to an active interaction between learners and teachers. Because in each learner learning has different abilities in understanding a concept, then the samples and definitions of each learner will also be different and it will be a nuance that will train learners to think creatively. This research is a descriptive research that aims to determine the effectiveness of conceptual learning in terms of creative thinking ability of learners. The subjects of the study were students of class X.2 SMA Negeri 1 Galesong Utara which amounted to 36 students. Data collection is done by using a learning result test that provides an overview of the creative thinking skills of learners that include the ability to think smoothly, the ability to think flexibly, the ability to think original, and the ability to think in detail. The result of descriptive statistic analysis shows that the effectiveness of concept learning is viewed from the ability of creative thinking in chemistry of learners in SMA Negeri 1 Galesong Utara on the subject matter of hydrocarbon equal to 44,38%.